Fundamentals of programming using Java - Currie, Edward (Thomson, 2006)
Aimed at students learning how to program for the first time, this is a focused introduction which stands out as an accessible first encounter with Java. Students work their way through carefully chosen examples and exercises – paced and structured for an intuitive progression. These drills will provide them with a sound and working knowledge of basic programming constructs. Taking an “objects later” approach, this book is designed for one semester courses with aim of providing a launch pad to later in depth OOP study. Concepts and principles are illustrated by everyday analogies and backed up by code examples which will help to clarify and anchor your understanding. Developed with support from Middlesex University Press and Global Campus.